1845 Del. Laws 10, A Supplement To The Act Entitled “An Act To Survey, Lay Out And Regulate the Streets Of Smyrna and for Other Purposes,” ch. 12, § 2 - (:unkn) unknown (General Publisher, 1845)
Imposed a duty on commissioners, justices of the peace, and constables to extinguish and prevent bonfires in the streets, lanes, and alleys. The duty also included the suppression and preventing discharge of guns, pistols, crackers, squibs, or fire-balls in the town limits.
--
Keywords: DISCHARGE